2003
DOI: 10.1029/2002wr001571
|View full text |Cite
|
Sign up to set email alerts
|

Diel cycles in dissolved metal concentrations in streams: Occurrence and possible causes

Abstract: [1] Substantial diel (24-hour) cycles in dissolved (0.1-mm filtration) metal concentrations were observed during low flow for 18 sampling episodes at 14 sites on 12 neutral and alkaline streams draining historical mining areas in Montana and Idaho. At some sites, concentrations of Cd, Mn, Ni, and Zn increased as much as 119, 306, 167, and 500%, respectively, from afternoon minimum values to maximum values shortly after sunrise. Arsenic concentrations exhibited the inverse temporal pattern with increases of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
150
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 51 publications
14
150
3
Order By: Relevance
“…Many studies have noted that diel cycles confound efforts to monitor contamination in streams using once-per-day sampling strategies [79]. Since sunlight is the main energy source of the ground surface, many biogeochemical phenomena affecting water follow a 24-h photocycle in response to sunlight.…”
Section: Analytical Methods For Measuring "Continuously"mentioning
confidence: 99%
“…Many studies have noted that diel cycles confound efforts to monitor contamination in streams using once-per-day sampling strategies [79]. Since sunlight is the main energy source of the ground surface, many biogeochemical phenomena affecting water follow a 24-h photocycle in response to sunlight.…”
Section: Analytical Methods For Measuring "Continuously"mentioning
confidence: 99%
“…Diurnal concentration ranges of several hundred percent have been documented [107]. Fluctuation varies by metal type and site conditions, and are driven by processes such as bioturbation, surface water and hyporheic flow, redox and photochemical reactions, precipitation/dissolution of solid mineral phases, and sorption processes.…”
Section: Contaminated Sediments As Stressorsmentioning
confidence: 99%
“…A rapidly growing body of literature documents the common occurrence of the diurnal flux of metals and organometals between sediments, biofilms, and overlying fresh and marine waters due to a number of processes [82,83,[100][101][102][103][104][105][106][107]. Diurnal concentration ranges of several hundred percent have been documented [107].…”
Section: Contaminated Sediments As Stressorsmentioning
confidence: 99%
“…It was previously reported that, in some rivers, the dissolved Zn concentrations increase from late afternoon to early morning (Jones et al, 2004;Nimick et al, 2003).Therefore, the pronounced variability of total dissolved Zn can be partly a result of the river water sampling at different times of the day, or it can be a consequence of the sample handling. Further investigation is thus required to clarify the causes for high short-term variability of total dissolved Zn in river water.…”
mentioning
confidence: 97%